2023
DOI: 10.1111/issj.12425
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agricultural credit disbursement on cereals yield in Odisha

Abstract: Realizing the significance of agricultural credit and considering millets and rice are the major crops in Odisha, this study proposes to examine the impact of agricultural credit disbursement (crop loan and term loan) on the yield of total cereals, millets and rice for the period 2000–01 to 2019–20. To examine the cointegration relationship among the variables, an autoregressive distributed lag (ARDL) bound F‐test, and to investigate the impact of agricultural credit on yield of total cereals, millets and rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…A substantial number of recent studies have been devoted to investigating the effects of agricultural credits on agriculture. While some of these studies used household/farm-level data such as Chandio et al (2017), Ullah et al (2020), Chandio et al (2021), Ma et al (2022), andYadav andRao (2022), some of them identified and addressed linkages using country-level data such as Misra et al (2016), Rehman et al (2017), Anh et al (2020), Seven and Tumen (2020), Manoharan and Varkey (2021), Chandio, Abbas, et al (2022), Chandio, Jiang, et al (2022), and Mahapatra and Jena (2023). The majority of the studies in the first category concluded that agricultural credits help to improve agricultural production efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A substantial number of recent studies have been devoted to investigating the effects of agricultural credits on agriculture. While some of these studies used household/farm-level data such as Chandio et al (2017), Ullah et al (2020), Chandio et al (2021), Ma et al (2022), andYadav andRao (2022), some of them identified and addressed linkages using country-level data such as Misra et al (2016), Rehman et al (2017), Anh et al (2020), Seven and Tumen (2020), Manoharan and Varkey (2021), Chandio, Abbas, et al (2022), Chandio, Jiang, et al (2022), and Mahapatra and Jena (2023). The majority of the studies in the first category concluded that agricultural credits help to improve agricultural production efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%